A study of flexural strength of prism using oil palm shell (ops) as a partial replacement of coarse aggregate - Mohd Abdul Hadi, Mohd Zaid (2017)
The purpose of this study was conducted to determine the use of oil palm shell (OPS) as coarse aggregate in concrete to replace granite in concrete mixture. The main objective of this study is to determine the workability, compressive strength and flexural strength of concrete using oil palm shells (OPS) as partial replacement of coarse aggregate compare to normal concrete. Experimental work was conducted in laboratory to determine the characteristic of oil palm shell concrete by using weight method. In this studies, there are different concrete mixes with different the combination of natural material content namely 0%, 5%, 10%, and 15%. There are 36 prism are provided with different ratio which are 0%, 5%, 10%, and 15% with partial replacement coarse aggregate in this project. The size of the prism is 150 X 150 X 750 mm. There are 36 cubes (150 X 150 X 150mm) are provided to get the average results of the compressive test. Each ratio have three sample specimen prepared for each concrete mixes. The laboratory tests conducted including sieve analysis, slump test, compressive strength test, and flexural strength. The results show that the oil palm shell concrete has strong compressive strength. Using the oil palm shell as aggregate in concrete can reduce the material cost in construction because of the low cost and abundant agricultural waste. In this experiment, there are several things that can be expected when finish. The following are some of the expected result for this experiment is to get higher compressive strength in lower density of concrete and to achieve the specified strength of OPS concrete that same to the control concrete at 28 days.